Las estructuras de los populismos: Difernciación funcional en el populismo latinoamericano - Adinolfi, Guilio (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The populisms never look like each other among them. The difference doesn't assist to its concrete phenomenology but to its structure and its function. The populism latinoameriaco represents this ambiguity formidably: in its the citizenship, the conformation of the power, the territory in that this it is applied, the funcionalización of the objectives expresses this different structure populist. The present work carries out a mere analysis of the structure and function of the current different populisms, and of it stops in the populism Latin American fruit of its historical, economic development and culture. The grade of objective democracy you can only achieve examining the structural-functional influence of the populism in the social life of a national community
Keywords: Populisms; Latin American Populism structural-funcionalismo; Objective democracy